User-capacity maximization in synchronous CDMA subject to RMS-bandlimited signature waveforms - Guess, T. (IEEE transactions on communications, 2004)
We consider the symbol-synchronous code-division multiple-access (CDMA) channel equipped with either a multiuser linear receiver or a multiuser decision-feedback receiver. The network, or user, capacity is defined to be the number of users that can be supported with available resources, such that every user achieves a certain quality of service (QoS). In this paper, the QoS threshold is given as a signal-to-interference ratio and the bandwidth is given as the root mean squared bandwidth of the received power spectral density of the users' transmitted waveforms. Given the QoS threshold and constraints on bandwidth and the sum of the users' received powers, we maximize user capacity for both the linear and decision-feedback receivers by optimally and jointly designing the users' signature waveforms and power-control polices.